2005
DOI: 10.1097/01.mao.0000179528.24909.ba
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cortisol and Other Stress-Related Hormones in Patients with M??ni??re??s Disease

Abstract: Patients with Ménière's disease have higher serum cortisol levels. It is suggested that these higher cortisol levels are rather the result than the cause of this chronic disease, because patients affected longer seem to have higher cortisol levels. The exact impact of these higher cortisol levels on the inner ear and endolymph homeostasis is yet unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…One obvious explanation for hippocampal atrophy in humans with BVD is that chronic stress from the disability leads to high circulating levels of cortisol. Short-term increases in cortisol have been reported in patients with vestibular disorders (Horii et al, 2007); however, long-term increases have been reported only in the case of Meniere’s disease and acoustic neuroma (Horner and Cazals, 2005; van Cruijsen et al, 2005). To date, every rat or guinea pig study that has examined corticosterone or cortisol levels (respectively) following unilateral or BVD has found no significant difference compared to sham controls up 5 months post-op.…”
Section: Discussionmentioning
confidence: 99%
“…One obvious explanation for hippocampal atrophy in humans with BVD is that chronic stress from the disability leads to high circulating levels of cortisol. Short-term increases in cortisol have been reported in patients with vestibular disorders (Horii et al, 2007); however, long-term increases have been reported only in the case of Meniere’s disease and acoustic neuroma (Horner and Cazals, 2005; van Cruijsen et al, 2005). To date, every rat or guinea pig study that has examined corticosterone or cortisol levels (respectively) following unilateral or BVD has found no significant difference compared to sham controls up 5 months post-op.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term elevations of cortisol and arginine vasopressin have been reported in patients with vestibular disorders (Horii et al, 2007); however, longer term elevations have been reported only in Meniere's disease and acoustic neuroma (Horner and Cazals, 2005;van Cruijsen et al, 2005), in the former case possibly because of its paroxysmal nature. No longterm studies have been carried out in patients with chronic bilateral vestibular loss.…”
Section: Why Should Manipulation Of the Vestibular System Have Effectmentioning
confidence: 94%
“…The changes in the limbic system are particularly interesting with respect to the hippocampal atrophy and related spatial memory deficits seen in patients with BVF [1]: Vestibular failure is known to be associated with an increase in the level of glucocorticoids [40], [41] and a reductive effect of these hormones on hippocampal volume was shown in various neuropsychiatric diseases [42]. Balance trained individuals have also shown a decrease in the anterior portion of the hippocampus [11], which is often related to emotional and chemical processing.…”
Section: Discussionmentioning
confidence: 99%